Effectiveness of the influenza vaccine at preventing hospitalization due to acute lower respiratory infection and exacerbation of chronic cardiopulmonary disease in Korea during 2010–2011 - Seo, Yu Bin; Hong, Kyoung-wook; Kim, In Seon; Choi, Won Suk; Baek, Ji Hyeon; Lee, Jacob; Song, Joon Young; Lee, Jin Soo; Cheong, Hee Jin; Kim, Woo Joo (Vaccine, 2013)
► We estimated the effectiveness of the influenza vaccine at preventing hospitalization. ► The overall vaccine effectiveness for preventing hospitalization was 32.5%. ► The effectiveness in patients aged ≥65 years with chronic heart disease was 72.6%. Influenza epidemics are accompanied by a considerable increase in hospitalization due to acute lower respiratory infection and exacerbation of underlying medical conditions. We estimated the effectiveness of the influenza vaccine at preventing hospitalization due to acute lower respiratory infection and new onset or acute exacerbation of chronic cardiopulmonary disease. During the peak influenza period in 2010–2011, we performed a multicenter, case–control, retrospective cohort study of patients who were hospitalized due to newly developed pneumonia, bronchitis, and bronchiolitis, or new onset or acute exacerbation of asthma, COPD, ischemic heart disease, and CHF. Controls were selected from outpatients who visited study hospitals but who were not hospitalized during the same study period. Controls were matched 1:1 to cases based on age, gender, and date of hospital visit. Univariate and multivariate logistic regression analyses were used to determine the effectiveness of the influenza vaccine at decreasing hospitalization. Between December 2010 and February 2011, 556 hospitalized subjects were identified. Age, gender, and body mass index (BMI) were similar between case and control groups. The influenza vaccination rate of the hospitalized and non-hospitalized patients was 42.4% and 52.2%, respectively (p<0.001). The overall vaccine effectiveness for preventing hospitalization was 32.5% (odds ratio 0.675, 95% confidence interval [CI] 0.486–0.937; p=0.019). Multivariate logistic analysis showed that influenza vaccination significantly reduced the risk of hospitalization, especially due to new onset or acute exacerbation of ischemic heart disease and CHF in patients aged 65 years and older (OR 0.274, 95% CI 0.114–0.658, p=0.004). The estimated vaccine effectiveness in these patients was 72.6%. Influenza vaccination reduced the rate of hospitalization among patients with underlying chronic heart disease, particularly those patients 65 years old and greater.